Legal Review Of Cooperation Between Indonesia And The Philippines In The Eradication Of Cross-Border Online Gambling - Muhammad Refly Kamal; Sofa Laela (Catalist Indo Publisher, 2026)
The development of information technology has brought various positive and negative impacts, one of which is the increase in cross-border online gambling practices, which are difficult to address solely through national legal instruments. Indonesia, as a country governed by the rule of law, faces serious challenges in suppressing online gambling practices, which often involve servers and players operating across borders. This creates new problems for countries that prohibit gambling. Therefore, Indonesia has established international cooperation, particularly with the Philippines, to address cross-border online gambling. This study aims to analyze the forms of international cooperation between Indonesia and the Philippines in enforcing cross-border online justice. The research method used is a normative juridical method with a regulatory and international legal approach. The results indicate that the Indonesia-Philippines extradition treaty, along with cooperation through Interpol and the Mutual Legal Assistance (MLA) mechanism, play a significant role in strengthening efforts to eradicate cross-border online gambling.